2021
DOI: 10.14710/jwl.9.2.186-197
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Education and Regional Income Level on Environmental Quality: Empirical Evidence from High Populated Country

Abstract: Indonesia is committed to implementing a sustainable development agenda by considering its quality and maintaining economic growth by improving public education and regional income. This study aims to estimate the relationship between education and regional income level with the environmental quality of Indonesian provinces. By applying the descriptive analysis and panel data regression, it is observed that regions with a high-level level of education and income are likely to have low environmental quality, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, the correlation analysis results showed that demographic estimates had a moderate correlation between education and income factors. This result is in line with a study conducted by Adrian and Khoirunurrofik (2021) [53] but not with that of Wolla and Sullivan (2017), who found this correlation to be very strong [54]. Meanwhile, a low positive association correlation occurred in employees aged 36-40 years with an average income of less than IDR three million per month.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the correlation analysis results showed that demographic estimates had a moderate correlation between education and income factors. This result is in line with a study conducted by Adrian and Khoirunurrofik (2021) [53] but not with that of Wolla and Sullivan (2017), who found this correlation to be very strong [54]. Meanwhile, a low positive association correlation occurred in employees aged 36-40 years with an average income of less than IDR three million per month.…”
Section: Discussionsupporting
confidence: 80%